The responsibility of the Registry holder for the Unpaid Community Fees of the Former Owner. The Proper Procedure for Reclaiming Them. The Actual Condition and its Problem in Gaining Access to the Land Register (Acta Judicial Journal, 2020)
The purpose of this paper is to determine the financial liability of the purchaser of the property subject to the Horizontal Property regime for the amounts owed for the support of general expenses by the former owner, and which would be the ideal procedure to demand this type of liability before the courts. In order to address this question, we will analyse the meaning and nature of the legal form of the 'real damage' to the property provided for in Article 9.1.3 e) of the LPH and, in the light of this analysis, we will study among the procedures provided for in our legal system, which would be the best way to assert this real damage in court and what the registration problems would be that would prevent the registration of the preference of the Community claim against other previous creditors.
Keywords: Real Condition, Payment Procedure, Registration, Responsibility, Acquirer Annotation, Registration, Credit Preference, Community of Owners